Fate of Dacryocystitis in the Community of Punjab (Medical Forum Monthly, 2020)
Objective: To study the Fate of Dacryocystitis in the Community of Punjab.Study Design: Retrospective studyPlace and Duration of Study: This study was conducted at the Idris Teaching Hospital Sialkot during March 2019 to March 2020.Materials and Methods: In this Retrospective study 100 patients with infection of lacrimal sac, Dacryocystitis, were recruited. Convenience sampling in sterile condition from lacrimal sac was used in this study.After registration of demographic data, sampling was performed by sterile swab from the pus out of the lacrimal sac. The exact time of sampling were recorded. Various media was used for bacterial cultivation. These media were blood agar, EMB, chocolate agar, and thioglycolate broth.Blood agar and EMB media were incubated in 37°c for 24 h and chocolate agar medium was incubated in specific CO2 concentration. Thioglycolate broth medium was used for anaerobic bacteria that may cause infection in 37°c incubator for 72 h. Biochemical tests were performed to identify bacteria in the case of colonies formation on the media. Various antibiotics such as amikacin, chloramphenicol, cefazolin, co-trimoxazole, vancomycin, doxycycline, tetracycline, erythromycin, and Gentamicin were used for studying the bacteria antibiotic resistance.SPSS version 15 was used for statistical analysis. Kolmogorov-Smirnov test for quantitative variables and chi-square test was used to evaluate the qualitative variables. Written informed consent was taken before taking history, examination and sample taking of the patient. The permission of Ethical Committee was taken before collecting the data and gets publishing in Medical Journal.Results: In this study, the mean age of participants was 49.36 ± 12.18 years which min and max ages were 19 and 66 respectively. Number of male and female patients was (72 (72%) female patients and 28 (28%) male patients). Sampling was performed in 53.3% of patients from right eye and 47.7%from left eye.Studying the type of obtained smear from pus of patients eyes in sterile condition was shown 46.7%, 6.7%, 16.7%, and 30% of smears were negative (normal), gram positive coccus, gram negative bacillus, and gram positive coccus with gram negative bacillus, respectively. The frequency of bacterial species was studied.Conclusion: In, the results obtained in this study show that gram-positive bacteria are the majority of bacteria causing Dacryocystitis, which is confirming previous studies. Although there are some results from other studies in contrast to our results regarding the prevalence of bacteria. It can be concluded that the type of bacterial infection can be linked to environmental conditions. On the other hand, this study showed that the best antibiotic for treatment of Dacryocystitis is Chloramphenicol. It should be noted that due to the variety of bacteria which can cause this disease, identification of bacterial contamination can be a great help in the treatment process.